Temporal branch of facial nerve: a normative study of nerve conduction Ramo temporal do nervo facial: um estudo normativo da condução nervosa - Paula Fabiana Sobral da Silva; Maria Carolina Martins de Lima; José Natal Figueiroa; Otávio Gomes Lins (Arquivos de Neuro-Psiquiatria)
The temporal branch of the facial nerve is particularly vulnerable to traumatic injuries during surgical procedures. It may also be affected in clinical conditions. Electrodiagnostic studies may add additional information about the type and severity of injuries, thus allowing prognostic inferences. The objective of the present study was to develop and standardize an electrophysiological technique to specifically evaluate the temporal branch of the facial nerve. METHOD: Healthy volunteers (n=115) underwent stimulation of two points along the nerve trajectory, on both sides of the face. The stimulated points were distal (on the temple, over the temporal branch) and proximal (in retro-auricular region). Activities were recorded on the ipsilateral frontalis muscle. The following variables were studied: amplitude (A), distal motor latency (DML) and conduction velocity (NCV). RESULTS: Differences between the sides were not significant. The proposed reference values were: A >0.4 mV, DML <3.9 ms and NCV >40 m/s. Variation between hemifaces should account for less than 60% for amplitudes and latency, and should be inferior to 20% for conduction velocity. CONCLUSION: These measurements are an adequate way for proposing normative values for the electrophysiological evaluation of the temporal branch. O ramo temporal do nervo facial é particularmente vulnerável a lesões traumáticas nos procedimentos cirúrgicos. Também pode ser acometido em várias condições clínicas. Estudos eletrodiagnósticos podem acrescentar informações quanto ao tipo e severidade das lesões. A pesquisa visa aperfeiçoar técnica eletrofisiológica para avaliação específica daquele ramo. MÉTODO: Voluntários (n=115) foram submetidos a estimulação eletroneurográfica em dois pontos, nas duas hemifaces. Estímulo distal na têmpora, estímulo proximal na região retroauricular. Foram registradas distâncias dos pontos de estímulo até pontos anatômicos da face; assim como variáveis relacionadas com o potencial de ação resultante. RESULTADOS: Houve grande variabilidade nas amplitudes, porém a diferença entre as hemifaces não foi significativa. Valores de referência propostos foram: amplitude (A) >0.4mV, latência motora distal (LMD) <3.9ms e velocidade de condução (VCN) >40m/s. Variabilidade aceitável entre os lados: LMD e A <60% e VCN <20%. CONCLUSÃO: Este estudo pode ser a ferramenta inicial para aplicações futuras no diagnóstico e seguimento de pacientes com lesões no ramo temporal.